PENGARUH PENGALAMAN, KOMPETENSI, DAN ORIENTASI PELANGGAN TERHADAP KUALITAS INTERAKSI TENAGA PENJUAL SERTA KINERJA PENJUALAN (Studi pada Tenaga Penjual PT. Penerbit Erlangga Cabang Semarang) - Ahmad Mudrik (ITB AAS INDONESIA, 2023)
The author focused on examines how to build quality of salesperson interaction and sales performance. The model is tested by Structural Equation Modelling Analysis on AMOS version 24 programs. Population of this thesis are Salespersons at PT Penerbit Erlangga Cabang Semarang with 113 respondents (all population). All hypotheses tested in this study are supported because their Critical Ratio tests show significant results with p< 0,05. Result of this research proved that salesperson experience has a positive impact on quality of salesperson interaction (CR=3.205), salesperson competency is positively related to quality of salesperson interaction (CR=4.274), customer orientation is positively related to quality of salesperson interaction (CR=2.679) and quality of salesperson interaction is positively related to sales performance (CR=7.833). Strategy result can take from this thesis showed at managerial implications that suggest using some strategies to enhance competency and quality of salesperson interaction in order to achieve sales performance. This thesis also recommends us to enhance each research variable and evaluate them to achieve sales performance. Keywords : Sales Performance, Salesperson Experience, Salesperson Competency, Customer Orientation, Quality of Salesperson Interaction.